Appetizers : 500 best-ever recipes : the ultimate collection of finger food and first courses, dips and dippers, snacks and starters, shown in 500 stunning photographs - Hildyard, Anne (Lorenz Books, 2009)
This unique compendium has drawn together recipes from across the world to help you create a selection of appetizers that everyone will enjoy, whatever the occasion